Assessment of Mineral Nutrient Efficiency in Genetically Diverse Spinach Accessions by Biochemical and Functional Marker Strategies - Rashid, Madiha; Yousaf, Zubaida; Din, Ahmad; Munawar, Muneeb; Aftab, Arusa; Riaz, Nadia; Younas, Afifa; Alaraidh, Ibrahim A.; Okla, Mohammad K.; AbdElgawad, Hamada (Frontiers in Plant Science, 2022)
The application of nitrogen fertilizers could have a positive effect on leafy crops in terms of high yield and nutrient contents. However, the crops with greater nitrate contents can have better nitrogen use efficiency by limiting nitrogen inputs in the form of chemical fertilizers. Moreover, the use of nutrient rich leafy crops could naturally decrease the risk factor of many growth issues in children and adults. Spinach is considered as the most desirable leafy vegetable in many countries around the globe, due to its taste and nutrient richness especially nitrates, oxalates, iron and calcium. However, the nutritional composition of a species could be directly influenced by a wide range of climatic conditions. The study was based on the evaluation of nutrient potential of globally available 30 spinach accessions by nutritional and functional molecular markers. The spectrophotometry technique was used to evaluate important mineral contents in the accessions. The accession 163310, from Pakistan was found to be rich in minerals (sodium, calcium, potassium, zinc, manganese) and nitrates. However, the oxalate contents were lesser, representing a negative correlation between mineral availability and oxalate accumulation in the leaves. The functional marker analysis was based on the availability of genes involved in oxalate metabolism and disease resistance in spinach. High level of polymorphism was observed among the accessions represented with 115 polymorphic bands out of 130 bands. Heat-map clustering represented the accessions from Asian countries (Pakistan, India, China and Iran) as the most adaptable accessions to the local environment. The correlation between nutritional and genetic analysis also revealed the nutrient richness of these accessions along with good oxalate metabolism and disease resistance. Hence these accessions could be considered as useful genotypes in future breeding programs.